1993
DOI: 10.1037/0022-3514.65.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive significance of female physical attractiveness: Role of waist-to-hip ratio.

Abstract: Evidence is presented showing that body fat distribution as measured by waist-to-hip ratio (WHR) is correlated with youthfulness, reproductive endocrinologic status, and long-term health risk in women. Three studies show that men judge women with low WHR as attractive. Study 1 documents that minor changes in WHRs of Miss America winners and Playboy playmates have occurred over the past 30-60 years. Study 2 shows that college-age men find female figures with low WHR more attractive, healthier, and of greater re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
830
8
25

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 1,058 publications
(906 citation statements)
references
References 37 publications
43
830
8
25
Order By: Relevance
“…Some of the specific bodily features shown to be important for judgments of attractiveness include the waist-to-hip ratio (Henss, 1995;Singh, 1993;Streeter & McBurney, 2003), body mass index (Tovée, Maisey, Emery, & Cornelissen, 1999), and breast size (Furnham, Swami, & Shah, 2006;Furnham & Swami, 2007). Indeed, although there are correlated preferences between facial and bodily attractiveness, some studies have shown that the face and body still make independent contributions to ratings of overall attractiveness (e.g., Currie & Little, 2009;Peters, Rhodes, & Simmons, 2007).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Some of the specific bodily features shown to be important for judgments of attractiveness include the waist-to-hip ratio (Henss, 1995;Singh, 1993;Streeter & McBurney, 2003), body mass index (Tovée, Maisey, Emery, & Cornelissen, 1999), and breast size (Furnham, Swami, & Shah, 2006;Furnham & Swami, 2007). Indeed, although there are correlated preferences between facial and bodily attractiveness, some studies have shown that the face and body still make independent contributions to ratings of overall attractiveness (e.g., Currie & Little, 2009;Peters, Rhodes, & Simmons, 2007).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Indeed, factors such as body mass index (BMI), body fat and waist-to-hip ratio (WHR) have been shown to correlate with attractiveness judgements (Singh, 1993;Tovée, Reinhardt, Emery, & Cornelissen, 1998;Weeden & Sabini, 2005), and are predictive of both health and fertility (Singh & Singh, 2011). For instance, slender figures with a low WHR and large breasts are often rated as more attractive and considered for relationships (Singh & Young, 1995), furthermore these features have been shown to correlate with high fecundity as measured by levels of sex hormones (Jasieńska, Ziomkiewicz, Ellison, Lipson, & Thune, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This possibility was systematically examined in this study. As measurements of BMI, WHR and chest size are strong predictors of attractiveness (Singh, 1993;Tovée et al, 1998;Weeden & Sabini, 2005), when assessing regional body dissatisfaction we included both objective measurements and subjective ratings of body parts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that waist-to-hip ratio (WHR) is an important index of female attractiveness (Dixson, Grimshaw, Linklater, & Dixson, 2011;Marlowe & Wetsman, 2001;Singh, 1993) that signals both a woman's fertility (Zaadstra et al, 1993) and her general health (Czernichow et al, 2011). WHR also changes over women's lifetimes (Kirschner & Samojlik, 1991) and so indicates residual reproductive value (Marlowe, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…WHR also changes over women's lifetimes (Kirschner & Samojlik, 1991) and so indicates residual reproductive value (Marlowe, 1998). It has therefore been proposed that WHR serves as an important ornament display (Perilloux, Webster, & Gaulin, 2010;Singh, 1993) and much is now known about the effects of this (e.g., Dixson, Sagata, Linklater, & Dixson, 2010;Karremans, Frakenhuis, & Arons, 2010;Platek & Singh, 2010;Singh, Dixson, Jessop, Morgan, & Dixson, 2010;Swami, Jones, Einon, & Furnham, 2009;Vaidya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%